ANALISIS PENGARUH MOTIVASI INTRINSIK DAN KEPEMIMPINAN OTENTIK TERHADAP KINERJA.(Studi Pada Laboran Perguruan Tinggi Negeri Dan Swasta Di Kota Bengkulu) - Santi - Zulmedia; Lizar - Alfansi; Praningrum - - (Universitas Bengkulu, 2021)
This study is to analyze how the influence of intrinsic motivation and authentic leadership on the performance (study on state and private university) laboratory assistants in Bengkulu. Motivation is very important in order to improve employee performance, especially intrinsic motivation. In addition to authentic leadership motivation, it is also studied with the results that there is an influence on performance. Methods this study was conducted with descriptive quantitative. As much as 87 respondents from 90 respondents gave a response. The tools used in this study is questionnaires, questionnaires distributed with offline. Sampling was carried out by nonprobability sampling with a total sampling technique or saturated sampling. The objective of this reseach is : (1). Intrinsic motivation has an effect on performance with a value of 0.012% (2). Authentic leadership has an effect on performance with a value of 0.02%. (3) Analyze influenze of work, intrinsic motivation and authentic leadership on the performance by partial. The research results were processed with SPSS version 16.0 for windows to test the validity and reliability using the Cronbach Alpha formula. Methods this study using multiple linear regression analysis. The coefficient of determination (R2) obtained 0.186 this shows that the predictor variabels of independent variables have an impact of 18,6% to dependent variable.